The relationship of credit management process and the level of non-performing loans of Majlis Amanah Rakyat in Sabah region / Mohd Rozie Mohd Damit, Norliza Abdullah and Siti Zaharah Hasan - Mohd Damit, Mohd Rozie; Abdullah, Norliza; Hasan, Siti Zaharah (2014)
Majlis Amanah Rakyat (MARA) is a government agency established under the purview of Ministry of Rural and Regional Development in order to assist the development of the socioeconomic of Bumiputera in Malaysia. Since its establishment, MARA continuously moves forward in line with the government agenda towards achieving Vision 2020. Due to the latest Pelan Strategik Transformasi MARA 2011-2015, it enforces MARA to stand alone through privatization in stages. Therefore, it attracts us to study the performance of MARA specifically Business Financing Division in Sabah Region. The initial idea of this study was to gauge the current level of NPLs of MARA prior to privatization. However, due to the NPL rate is too high, therefore, the purpose of this study has been changed to study the relationship of credit management process and the level of the NPLs of MARA in Sabah Region. The methodology used for this study is a combination of Quantitative (Questionnaire) and Qualitative (Interview) technique. The data from the questionnaire evaluated using Multiregression Analysis as to measure the relationship the independent variables and dependent variable while the Qualitative technique is through semi-structured interview by hoping that the main objective of the study is satisfied.